2020
DOI: 10.1186/s11689-020-09315-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of lovastatin combined with an open-label treatment of a parent-implemented language intervention in youth with fragile X syndrome

Abstract: Background: The purpose of this study was to conduct a 20-week controlled trial of lovastatin (10 to 40 mg/day) in youth with fragile X syndrome (FXS) ages 10 to 17 years, combined with an open-label treatment of a parentimplemented language intervention (PILI), delivered via distance video teleconferencing to both treatment groups, lovastatin and placebo. Method: A randomized, double-blind trial was conducted at one site in the Sacramento, California, metropolitan area. Fourteen participants were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 72 publications
3
43
0
Order By: Relevance
“…ELS has several potential advantages compared to typical norm-referenced standardized tests [30], such as the Receptive and Expressive subscales of the Mullen Early Scales [37], the Peabody Picture Vocabulary Test-4th edition [38], the Preschool Language Scale-5 [39], the Clinical Evaluation of Language Fundamentals [40], and the Comprehensive Assessment of Spoken Language [41], all of which have been used in clinical trials for FXS [42][43][44][45]. First, ELS interactive contexts are more closely aligned with performance in real-world contexts, and thus, performance is more likely to be generalizable to activities that are functional and meaningful for the individual [46].…”
Section: Expressive Language Samplingmentioning
confidence: 99%
“…ELS has several potential advantages compared to typical norm-referenced standardized tests [30], such as the Receptive and Expressive subscales of the Mullen Early Scales [37], the Peabody Picture Vocabulary Test-4th edition [38], the Preschool Language Scale-5 [39], the Clinical Evaluation of Language Fundamentals [40], and the Comprehensive Assessment of Spoken Language [41], all of which have been used in clinical trials for FXS [42][43][44][45]. First, ELS interactive contexts are more closely aligned with performance in real-world contexts, and thus, performance is more likely to be generalizable to activities that are functional and meaningful for the individual [46].…”
Section: Expressive Language Samplingmentioning
confidence: 99%
“…In addition, these measures all display minimal practice effects and have strong test-retest reliability for individuals with FXS and DS in the age range interest, which is important in longitudinal studies that, by definition, involved repeated administration of the same measures [56,63]. Finally, intervention studies in individuals with different neurodevelopmental disorders have shown change in various ELS measures in the face of a lack of change in standardized tests [64][65][66]. Thus, we used naturalistic conversation and narration language sampling techniques in a longitudinal design and computed these diverse measures of expressive language performance in verbal individuals with ID associated with DS and with FXS.…”
Section: Syndrome Comparison Studies Of Expressive Language Developmentmentioning
confidence: 99%
“…Future studies will be needed to compare the efficacy between behavioral treatment with FCT and pharmacological treatment in FXS. Ultimately, it is possible that a combination of pharmacological and behavioral treatment may be the most beneficial treatment strategy [ 13 , 72 ].…”
Section: Discussionmentioning
confidence: 99%